Motivating the Motivated: Role of Engagement Commitment in Enhancing Performance - Kurniyati, Etiek; Khajar, Ibnu (Universitas Semarang, 2025)
The purposes of this study is to identify and analyze the influence of Employee Engagement and Organizational Commitment on Employee peroformance, with Intrinsic Motivation as a mediating factor. This research adopts an Explanatory Research approach. The sample consists of nurses working at Semarang Regency Hospital, selected using Slovin formula. The resutls indicate that Employee Engagement and Organizational Commitment do not have an effect on Employee Performance. However, both Employee Engagement and Organizational Commitment have a positive and significant effect on Intrinsic Motivation. Intrinsic Motivation has a positive and significant effect on Employee Performance and serves as a significant mediating variable between Employee Engagement, Organizational Commitment, and Employee Performance